A comparison of dexmedetomidine versus midazolam – Fentanyl for sedoanalgesia andstable hemodynamic parameters, during colonoscopy under Monitored Anesthesia Care. (MAC) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background:colonoscopy is routinely done under local anesthesia but it is stressful. Nowadays concept of conscious sedation or monitored Anesthesia care with mild sedoanalgesia is getting popular.Aim& Objective:The aim of our study was to compare the effects of dexmedetomidine versus midazolam Fentanyl combination on perioperative hemodynamics, sedation, pain, satisfaction and recovery scores during colonoscopy. Study design: Randomized comparative observational studyMaterial and methods:A total of 60 adult patients of ASA grade l/ll were included in the study. Patients were randomly allocated to two groups.In Group A Midazolam 0.02 mg/ kg and fentanyl citrate 1 mcg/ kg were administered intravenously followed by 0.5 ml/ kg/ hr. of Normal saline.In Group B An initial loading dose of 1 mcg/ kg dexmedetomidine was administered intravenously in 10 min to cases before the procedure and followed by continuous infusion dose of 0.5 mcg/ kg /hr.Incremental dose of 1 mcg/ kg fentanyl citrate was administered intravenously immediately before the procedure. Peripheral oxygen saturation (SpO2), mean arterial pressure (MAP), heart rate (HR), Ramsay Sedation Scale (RSS), Numeric Rating Scale (NRS) scores and colonoscopist satisfaction scores of the cases were recorded.Results:Although statistically significant values were not detected between the two groups with regard to mean arterial pressure.In Group I heart rates were higher and Spo2 scores were lower in a statistically significant manner. When the groups were compared with regard to RSS, the RSS scores of Group A at the 10th and 15th minutes were significantly lower than Group B. There was no statistically significant difference between the two groups when compared with regard to NRS scores. Satisfaction scores were significantly lower in Group B.Conclusion:Dexmedetomidine provides more efficient hemodynamic stability, higher Ramsay sedation scale scores, higher satisfaction scores and lower NRS score. So dexmedetomidine can be used safely as a sedoanalgesic agent.
Keywords: dexmedetomidine versus midazolam; Fentanyl for sedoanalgesia; stable hemodynamic parameters; colonoscopy; Anesthesia Care; Monitored Anesthesia Care. (MAC)